A simplified model for analysis of unreinforced masonry shear walls under combined axial, shear and flexural loading - Ghiassi, Bahman (2012)
A macro computational model is presented in this study for simulating the nonlinear static behavior of masonry walls. The adopted strategy is based on modeling the nonlinear behavior of masonry elements considering it as an orthotropic material and then extending it with a simple method to masonry walls. The model is capable of considering shear and flexural deformations in the global behavior. It can also predict all possible failure modes in masonry such as compressive crushing, bed-joint sliding, rocking, diagonal tension cracking and diagonal stepped cracking. Suitable material constitutive models and failure criteria are adopted for each failure mode under biaxial stress states. The contact density model has been modified and used for simulating the shear behavior in the masonry joints. It is shown that the analysis results are in good agreement with experimental observations, while the analysis time is significantly lower comparing to the usual numerical approaches such as finite element methods. Moreover, the proposed model can be used as a macro-model for analysis of large structures and provides reasonable accuracy.